An In-Depth Exploration of Route Prediction Algorithms: A Comprehensive Analysis - Soni, Nidhi; Jangra, Ajay (International Journal of Computer Sciences and Engineering, 2023)
In recent years, route prediction and planning services have gained significant popularity, thanks to the abundance of geo-information and the rise of various applications. With the increasing global population and widespread adoption of smartphones and GPS devices, a vast amount of geo-data is being generated. Route prediction plays a crucial role in reducing travel time, effort, and cost. In this project, our main objective is to develop a web-based application that can generate scalable travel itineraries. To achieve this, we propose the Multiple-Destination Route Prediction (MDRP) algorithm, which predicts optimal paths based on geographical data. These geographical data points are then visualized on a map using a map matching tool, providing the user with the final results. Real datasets, publicly available, Utilizing Road network spatial data along with GPS traces collected from users, are used to conduct experiments. Generating multiple valid node sequences of varying lengths in a sequential manner poses a challenge due to the need for multiple passes through the database. However, the experiments conducted on these real datasets have demonstrated that our proposed MDRP algorithm efficiently predicts optimized shortest paths to multiple locations.